2004
DOI: 10.1111/j.1462-8902.2004.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of orlistat on obesity‐related diseases – a six‐month randomized trial

Abstract: Orlistat plus a mildly reduced-calorie diet produced clinically meaningful weight loss and improvements in risk factors in overweight and obese patients with poorly controlled type 2 diabetes, hypertension or hypercholesterolaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 22 publications
4
26
0
Order By: Relevance
“…We investigated obese patients over the first 3 months because in studies carried out on obesity, weight loss in these patients was often observed over the first 3 months, while it diminished dramatically after this period [20,21,22]. There was a significant weight loss in the first 3 months in patients who were enrolled in our study, which is consistent with data in the literature.…”
Section: Discussionsupporting
confidence: 80%
“…We investigated obese patients over the first 3 months because in studies carried out on obesity, weight loss in these patients was often observed over the first 3 months, while it diminished dramatically after this period [20,21,22]. There was a significant weight loss in the first 3 months in patients who were enrolled in our study, which is consistent with data in the literature.…”
Section: Discussionsupporting
confidence: 80%
“…Orlistat improves adipocyte factors associated with hypertension, such as adiponectin, free fatty acids, IL-6, and leptin [64][65][66][67][68][69][70], and, clinically, orlistat improves blood pressure [72][73][74][75]. Orlistat improves adipocyte factors associated with dyslipidemia, such as adiponectin and free fatty acids [64,65,67,68] and, clinically, orlistat improves lipid blood levels [66,72,73,76,77].…”
Section: Treatment Of Adiposopathymentioning
confidence: 93%
“…Physiologically, weight loss with orlistat [62•,63] has favorable effects upon adipocyte factors associated with T2DM, such as adiponectin, free fatty acids, IL-6, leptin, resistin, and tumor necrosis factor-α [64][65][66][67][68][69][70], and, clinically, orlistat improves glucose metabolism [66,[71][72][73]. Orlistat improves adipocyte factors associated with hypertension, such as adiponectin, free fatty acids, IL-6, and leptin [64][65][66][67][68][69][70], and, clinically, orlistat improves blood pressure [72][73][74][75].…”
Section: Treatment Of Adiposopathymentioning
confidence: 99%
“…To review further, Table 1 [6,8,[9][10][11][12][13][14][15][16] gives an overview of 10 randomized controlled trials in patients with T2D that reported research findings of benefits for the orlistat-treated group. Trials are listed by the length of time to the outcome measurement (6 months to 1 year).…”
Section: Obesity Trialsmentioning
confidence: 98%